TRAP1 enhances Warburg metabolism through modulation of PFK1 expression/activity and favors resistance to EGFR inhibitors in human colorectal carcinomas. Issue 12 (30th October 2020) - Maddalena, Francesca; Condelli, Valentina; Matassa, Danilo Swann; Pacelli, Consiglia; Scrima, Rosella; Lettini, Giacomo; Li Bergolis, Valeria; Pietrafesa, Michele; Crispo, Fabiana; Piscazzi, Annamaria; Storto, Giovanni; Capitanio, Nazzareno; et al.
Abstract : Metabolic rewiring is a mechanism of adaptation to unfavorable environmental conditions and tumor progression. TRAP1 is an HSP90 molecular chaperone upregulated in human colorectal carcinomas (CRCs) and responsible for downregulation of oxidative phosphorylation (OXPHOS) and adaptation to metabolic stress. The mechanism by which TRAP1 regulates glycolytic metabolism and the relevance of this regulation in resistance to EGFR inhibitors were investigated in patient‐derived CRC spheres, human CRC cells, samples, and patients. A linear correlation was observed between TRAP1 levels and 18 F‐fluoro‐2‐deoxy‐glucose ( 18 F‐FDG) uptake upon PET scan or GLUT1 expression in human CRCs. Consistently, TRAP1 enhances GLUT1 expression, glucose uptake, and lactate production and downregulates OXPHOS in CRC patient‐derived spheroids and cell lines. Mechanistically, TRAP1 maximizes lactate production to balance low OXPHOS through the regulation of the glycolytic enzyme phosphofructokinase‐1 (PFK1); this depends on the interaction between TRAP1 and PFK1, which favors PFK1 glycolytic activity and prevents its ubiquitination/degradation. By contrast, TRAP1/PFK1 interaction is lost in conditions of enhanced OXPHOS, which results in loss of TRAP1 regulation of PFK1 activity and lactate production. Notably, TRAP1 regulation of glycolysis is involved in resistance of RAS‐wild‐type CRCs to EGFR monoclonals. Indeed, either TRAP1 upregulation or high glycolytic metabolism impairs cetuximab activity in vitro, whereas TRAP1 targeting and/or inhibition of glycolytic pathway enhances cell response to cetuximab. Finally, a linear correlation between 18 F‐FDG PET uptake and poor response to cetuximab in first‐line therapy in human metastatic CRCs was observed. These results suggest that TRAP1 is a key determinant of CRC metabolic rewiring and favors resistance to EGFR inhibitors through regulation of glycolytic metabolism. Abstract : Here, we show that TRAP1 modulates glycolytic metabolism by regulating PFK1 activity/stability. In a high TRAP1 background, TRAP1 inhibits cellular respiration and interacts with PFK1 on the ER and this enables PFK1 glycolytic activity preventing its ubiquitination/degradation. In a low TRAP1 background, cellular respiration is upregulated and PFK1 activity reduced due to increased ubiquitination/degradation and this results in loss of TRAP1 control on glycolytic cascade. The increased levels of citrate, observed in conditions of enhanced cellular respiration, are responsible for the inhibition of PFK1 activity, and this results in enhancement of PFK1 ubiquitination/degradation.